Causal Relationship between Inflation Rate, Exchange Rate, Interest Rate and Stock Market Returns - Neelum Nawab; Sadiqeen Ahmad; Muhammad Tahir Khan (UW Journal of Management Sciences, 2021)
Purpose: The purpose of this study is to provide empirical evidence on the causal relationship between interest rate (INTR), exchange rate (EXR), inflation rate (INFR) and stock prices return (SPR) in Pakistan for twenty years from 1998-2018. Design and Methodology: The research study first used Augmented Dickey Fuller (ADF) unit root test to check the stationarity of the data at level and at first differences, after determining the stationarity of the data next technique that is Johansen Co-integration Technique was used to determine the long term equilibrium relationship among variables. Finally, Granger Causality Test was used to find the causal relationship among the variables, by using this technique, direction of causality that is unidirectional, bidirectional and no direction causality was investigated. Findings: The results from Granger Causality have shown a unidirectional causality running from EXR to SPR and from INTR to SPR and no causality was observed between INFR and SPR respectively. Implications: The overall evidence, however, appears to show that Pakistan equity market efficiently incorporated much of the INTR and EXR information in its SPR. The study have important implications for investors.